2012
DOI: 10.5539/ibr.v5n7p97
|View full text |Cite
|
Sign up to set email alerts
|

CSR within SMEs: Literature Review

Abstract: Although CSR has traditionally been associated with big business, the SME business sector is such a significant sector worldwide in terms of the economic, environmental and social impact it makes, that attention has been turned to discussion and analysis of principles and practice of CSR in small and medium size businesses. SMEs are not merely small versions of big businesses, so as a result a particularly fast-growing body of academic work has become focused on commitment to CSR in the sector. As a result, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 37 publications
1
64
1
4
Order By: Relevance
“…The theory of dynamic capabilities and economic theory mention that, as the company grows in size and age, business strategies such as CSR actions increase and consequently increase financial results (Teece, 2007;Zahra, Neubaum, & El-Hagrassey, 2002). However, our results are not under this guideline, this is mainly due to the fact that the size of the companies under study are smaller and lack the resources and dynamic capacities to execute CSR strategies, which limits the increase of profitability (Kechiche & Soparnot, 2012;Lepoutre & Heene, 2006).…”
Section: Discussioncontrasting
confidence: 52%
“…The theory of dynamic capabilities and economic theory mention that, as the company grows in size and age, business strategies such as CSR actions increase and consequently increase financial results (Teece, 2007;Zahra, Neubaum, & El-Hagrassey, 2002). However, our results are not under this guideline, this is mainly due to the fact that the size of the companies under study are smaller and lack the resources and dynamic capacities to execute CSR strategies, which limits the increase of profitability (Kechiche & Soparnot, 2012;Lepoutre & Heene, 2006).…”
Section: Discussioncontrasting
confidence: 52%
“…Nevertheless, several studies on CSR in SMEs have concentrated on five major areas: the definitions of CSR by SMEs, characteristics of SMEs, motivations of CSR in SMEs, barriers to CSR studies in SMEs, and CSR activities in SMEs [7,8]. Masurel [2] further observed that there have been very few empirical studies on CSR outcomes or impacts of CSR in SMEs.…”
Section: Csr In Smesmentioning
confidence: 99%
“…Thus, the most obvious gap in the extant literature pertains to the limited number of studies on the link between CSR and firm performance from developing countries' perspectives [6,7]. Kechiche and Soparnot [8] called for the investigation of the links between responsible management for SMEs and financial performance in developing countries. Additionally, those that have examined the link between CSR and firm performance have used cross sectional study designs (e.g., [2,5]), and there are few longitudinal studies examining this association, making it impossible to establish the presence or absence of a causal effect.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the inner structure and relationships of SMEs, such as the flat hierarchy, stimulate CSR involvement (Kechiche & Soparnot, 2012, p.99). One of the relevant factors in stimulating CSR is the network around an SME (Kechiche & Soparnot, 2012;Louche & Michotte, 2011Worthington et al, 2008. Relationships with various communities, especially the local ones are critical in getting involved in social causes.…”
Section: Are Smes Responsible In Different Ways Compared To Corporatimentioning
confidence: 99%
“…Various literature reviews, both investigating the SME sector (Kechiche & Soparnot, 2012;Louche & Michotte, 2011;Vázquez-Carrasco & López-Pérez, 2013) and the large corporations (Schmitz & Schrader, 2015), show an increase of interest in this topic, visible in the growing number of studies and in the diversity of themes approached. The impact of CSR is studied by heterogeneous research, highlighting both financial outcomes, as well as other types of benefits.…”
Section: Introductionmentioning
confidence: 99%